2018
DOI: 10.1097/prs.0000000000003988
|View full text |Cite
|
Sign up to set email alerts
|

Corset Trunkplasty: Recommended with Abdominal Skin Laxity and Open Cholecystectomy Scar

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…10 In our patient with an open cholecystectomy scar, it was established that the rate of complications, especially flap necrosis, increases if traditional abdominoplasty is performed. 3,5,6 As of other types of abdominal scars, the literature stands in an area of uncertainty and controversy when it comes to complication rate in patients undergoing traditional abdominoplasty. De Castro et al showed that the risk grows higher in patients with supraumbilical scars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In our patient with an open cholecystectomy scar, it was established that the rate of complications, especially flap necrosis, increases if traditional abdominoplasty is performed. 3,5,6 As of other types of abdominal scars, the literature stands in an area of uncertainty and controversy when it comes to complication rate in patients undergoing traditional abdominoplasty. De Castro et al showed that the risk grows higher in patients with supraumbilical scars.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, many surgeons refrain from abdominoplasty in high-risk patients. One of the populations at high risk of postoperative complications are patients with previous vertical or subcostal abdominal scars that have disruptive effect on the abdominal wall blood supply, undermining the results of abdominoplasty [3][4][5] ; patients with Kocher incision after open cholecystectomy pose a selection dilemma, as the rate of complications, especially wound healing issues, increases when traditional abdominoplasty is performed in patients with such incision. 3,6 To overcome this disadvantage, we propose a refinement in traditional abdominoplasty where the upper flap is treated as a delayed flap, as will be demonstrated in this case report, with excellent results and no postoperative complications.…”
mentioning
confidence: 99%
“…2,3 To minimize complications of previous scars in abdominoplasty, some authors suggest lipoabdominoplasty and limited undermining, placing less tension on the flap closure, delaying it, or using a different type of resection, such as reverse or Corset abdominoplasty. 2,[4][5][6] The possibility of inferior aesthetic results and the high risk of complications must be carefully discussed with these patients. Noninvasive methods for evaluating abdominal wall perfusion may help surgeons decide on the best option in the presence of a subcostal scar.…”
Section: Introductionmentioning
confidence: 99%